The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1109/tdmr.2004.831992
|View full text |Cite
|
Sign up to set email alerts
|

A Drain Avalanche Hot Carrier Lifetime Model for n- and p-Channel MOSFETs

Abstract: A simple and physical drain avalanche hot carrier lifetime model has been proposed. The model is based on a mechanism of interface trap generation caused by recombination of hot electrons and hot holes. The lifetime is modeled as. The formula is different from the conventional -sub model in that the exponent of is 2, which results from the assumed mechanism of the two-carrier recombination. It is shown that the mechanism gives a physical basis of the empirical -sub model for NMOSFETs. The proposed model has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Early researches reported that pMOSFETs showed the worst degradation at DAHC and room temperature if cryogenic operation is unnecessary [1][2], but, based on 0.13 µm technology, our recent study showed that the worst case of HC has switched from DAHC to CHC and from low to high temperature. And the mechanisms pMOSFETs' degradation are related to bias temperature instability (BTI) effect plus reverse temperature effect [3][4].…”
Section: Introductionmentioning
confidence: 88%
“…Early researches reported that pMOSFETs showed the worst degradation at DAHC and room temperature if cryogenic operation is unnecessary [1][2], but, based on 0.13 µm technology, our recent study showed that the worst case of HC has switched from DAHC to CHC and from low to high temperature. And the mechanisms pMOSFETs' degradation are related to bias temperature instability (BTI) effect plus reverse temperature effect [3][4].…”
Section: Introductionmentioning
confidence: 88%
“…3,4) Additionally, owing to the activation energy provided by the recombination of electrons and holes, MOSFETs in the drain avalanche HC [DAHC -stressed at maximal substrate current I bm where V g ¼ ð1=3 {1=2ÞV d ] mode have traditionally been treated as the worst bias conditions. [5][6][7] Provided cryogenic operation is unnecessary, then the DAHC at room temperature constitutes the worst stress condition for testing the HC reliability of MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of scaling is to reduce device dimensions without disturbing its performance. In the literature, different circuit and technological solutions have been proposed, to study the scaling effects in sub‐micron MOSFETs (Takeda et al ; 1982; Park et al , 1996; Iniguez and Fjeldly, 1997; Koike and Tatsuuma, 2002; Anil et al , 2003). Duncan et al (1998) studied the effects of various scaling techniques on hot carrier behavior in different kinds of n ‐channel MOSFET structures.…”
Section: Introductionmentioning
confidence: 99%